TYPOLOGY OF RUSSIAN CRITICISM (CLASSIFICATION BY TRENDS AND TRENDS, METHODS, SUBJECTS OF CRITICAL CREATIVITY) - M.A. Jurayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article classifies the typology of Russian criticism by directions and trends, methods, subjects of critical creativity. When covering the topic, the conclusions of many scientists were used.